Attitudes, knowledge and practices of healthcare workers regarding occupational exposure of pulmonary tuberculosis - Lesley T. Bhebhe; Cornel Van Rooyen; Wilhelm J. Steinberg (African Journal of Primary Health Care & Family Medicine, 2014)
Background: Healthcare-associated tuberculosis (TB) has become a major occupational hazard for healthcare workers (HCWs). HCWs are inevitably exposed to TB, due to frequent interaction with patients with undiagnosed and potentially contagious TB. Whenever there is a possibility of exposure, implementation of infection prevention and control (IPC) practices is critical. Objective: Following a high incidence of TB among HCWs at Maluti Adventist Hospital in Lesotho, a study was carried out to assess the knowledge, attitudes and practices of HCWs regarding healthcare-associated TB infection and infection controls. Methods: This was a cross-sectional study performed in June 2011; it involved HCWs at Maluti Adventist Hospital who were involved with patients and/or sputum. Stratified sampling of 140 HCWs was performed, of whom, 129 (92.0%) took part. A self-administered, semi-structured questionnaire was used. Results: Most respondents (89.2%) had appropriate knowledge of transmission, diagnosis and prevention of TB; however, only 22.0% of the respondents knew the appropriate method of sputum collection. All of the respondents (100.0%) were motivated and willing to implement IPC measures. A significant proportion of participants (36.4%) reported poor infection control practices, with the majority of inappropriate practices being the administrative infection controls (> 80.0%). Only 38.8% of the participants reported to be using the appropriate N-95 respirator. Conclusion: Poor infection control practices regarding occupational TB exposure were demonstrated, the worst being the first-line administrative infection controls. Critical knowledge gaps were identified; however, there was encouraging willingness by HCWs to adapt to recommended infection control measures. Healthcare workers are inevitably exposed to TB, due to frequent interaction with patients with undiagnosed and potentially contagious TB. Implementation of infection prevention and control practices is critical whenever there is a possibility of exposure.